R/Avr gene expression study of Rpi-vnt1.1 transgenic potato resistant to the Phytophthora infestans clonal lineage EC-1 - Roman, M.L.; Izarra, M.; Lindqvist-Kreuze, H.; Rivera, C.; Gamboa, S.; Tovar, J.C.; Forbes, G.A.; Kreuze, Jan F.; Ghislain, M. (Springer, 2017)
The Avr avirulence gene of Phytophthora infestans and R gene of the potato are the genetic components of the gene-for-gene interaction resulting in host plant resistance. This effector-triggered immunity has been recently exploited to generate extreme resistance to late blight in potato by genetic engineering. The choice of the R genes, their number forming a R gene stack, and the pathogen Avr gene diversity will likely determine how long this extreme resistance will last. Here, we report on a comparative study on the Rpi-vnt1.1 gene which originated from Solanum venturii, and was introduced in the potato variety ‘Desiree’ by genetic transformation, and the Avr-vnt1 gene from two isolates of the EC-1 lineage of P. infestans. EC-1 was reported previously as not expressing the Avr-vnt1 gene and, therefore, being virulent on Rpi-vnt1.1 transgenic plants. Unexpectedly, whole-plant resistance assays identified 5 out of 52 transgenic events as resistant to two isolates of P. infestans, POX067 and POX109, belonging to the EC-1 lineage. We demonstrated that in both isolates, the Avr-vnt1.1 gene was expressed at a low level. Expression of the Rpi-vnt1.1 gene was shown to be rapidly increased by two-fold and subsequently to have steady state expression for at least 5 days after the inoculation. The Rpi-vnt1.1 gene in addition to other R genes as a stack in farmers’ preferred varieties will confer extreme resistance to late blight disease and rotations of plants with different R-gene-stack in time is likely to last longer than plants with single R gene.